PARADOKSALITAS DI BALIK KEMEGAHAN BOROBUDUR - Bambang Suharto (Universitas Gadjah Mada, 2012)
This article aimes at exploring the destination organization management of Borobudur temple. The approach methodused in this writing is descriptive interpretative of organization behavior. The data was collected from literaturestudy, participated observation, and the discussions in the seminars. The research’s fi ndings show that the successof organizations managing Borobudur has been focused on the fulfi llment of legal and economic responsibilitiesrather than social ones, as mandated by the Ministry of State-Owned Enterprises in law Nomor 40 of 2007 andLaw Nomor 10 of 2009. Moreover, it is aggravated by the behavior of urban society, members of which all havetheir own interets. Finally, the local community will become more marginalized if the government does not takeany serious actions taken to empower them immediately.